Systematic Review Of Step-NC-Based Inspection - Yusof, Yusri; Saif, Yazid; lliyas Ahmed, Maznah; Latif, Kamran; Abdul Kadir, Aini Zuhra (Springer, 2020)
Closed-loop inspection manufacturing (CLIM) and computer-aided inspection planning (CAIP) have increasingly been evolved into a size method that can be used to look at fashions in the industrial area with a number of methods. CAIP is hastily carried out in the gadget and will become an indispensable phase of the production system. Numerous scientific findings that tackle the theme from exclusive perspectives are accompanied by CLIM and CAIP in the measuring process. A systematic overview of these heterogeneous methods can be considered vital for CLIM to become aware of the ways in which CAIP can be used in your personal context. Thus, this systematic review of literature aims to analyze current inspection article and use of CLIM in CNC machines, assess heritage research to create a steady taxonomy, and provide a framework for forthcoming CLIM lookup in accordance with CAIP in the desktop gadget to enhance product quality. The consequences of this study provide a comprehensive taxonomy and a define in terms of the advanced features of this emerging technology. Articles on CAIP and CLIM, system-based technology, implementation of STEP/STEP-NC, and feature-based technology were discussed. As a result, various CLIM lookup findings regarding the machining machine tended to the center of attention rather on the VISION/aspects of the ISO14649-based computing device and further on inspection process planning perspectives, as well as factors indicating CLIM in technologies. This review paper will strengthen this study by supplying a deep analysis of the present facts to shut down the hole and lengthen the current literature.